2019
DOI: 10.1038/s41598-019-41843-5
|View full text |Cite
|
Sign up to set email alerts
|

Different bacterial and viral pathogens trigger distinct immune responses in a globally invasive ant

Abstract: Invasive species populations periodically collapse from high to low abundance, sometimes even to extinction. Pathogens and the burden they place on invader immune systems have been hypothesised as a mechanism for these collapses. We examined the association of the bacterial pathogen ( Pseudomonas spp.) and the viral community with immune gene expression in the globally invasive Argentine ant ( Linepithema humile (Mayr)). RNA-seq analysis found evidence for 17 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Ants are potential hosts of honey bee viruses [24,32,[35][36][37][38][39], and viral replication has been confirmed for chronic bee paralysis virus in the carpenter ant, Camponotus vagus [35], for DWV and Kashmir bee virus in the Argentine ant, Linepithema humile [37,39] and DWV in Myrmica rubra [24]. Although these viruses can modify ant immune responses [40], no study has yet experimentally addressed the clinical symptoms of these viruses in ants, either at the individual host or colony level, to confirm that ants are biological hosts. As ants provide essential ecosystem services and play a key role in terrestrial ecosystems [41,42], the potential negative impacts of virus transmission between managed honey bees and ants might pose a threat to ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Ants are potential hosts of honey bee viruses [24,32,[35][36][37][38][39], and viral replication has been confirmed for chronic bee paralysis virus in the carpenter ant, Camponotus vagus [35], for DWV and Kashmir bee virus in the Argentine ant, Linepithema humile [37,39] and DWV in Myrmica rubra [24]. Although these viruses can modify ant immune responses [40], no study has yet experimentally addressed the clinical symptoms of these viruses in ants, either at the individual host or colony level, to confirm that ants are biological hosts. As ants provide essential ecosystem services and play a key role in terrestrial ecosystems [41,42], the potential negative impacts of virus transmission between managed honey bees and ants might pose a threat to ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Such population structure has been shown to facilitate the horizontal transmission of pathogens among nests of invasive ants in an extensively large area due to the lack of visible nest boundaries that allows inter-nest interactions [ 39 ]. It would be interesting to test if DWV can be transmitted horizontally among ant nests within the same supercolony, especially given that DWV (and other honey bee viruses) is generally present at a low titer within ants [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data, coupled with a similar pattern in another population (Australia) of this ant by Cooling et al [ 48 ], suggest that the window for successful interspecific transmission of DWV is likely narrow in the yellow crazy ant. Although speculative, additional factors such as the immune responses of ants may have been involved [ 46 ]. For example, we argue that competition between coinfecting pathogens may partially explain DWV’s low incidence in the yellow crazy ant.…”
Section: Discussionmentioning
confidence: 99%
“…Host/pathogen interactions can be unique and much work remains to be done to fully understand specific immune responses associated with different pathogens and symbionts in Argentine ants. In Argentine ants, it has been shown that different viruses can trigger distinct immune responses, sometimes associated with specific virus families (Lester et al 2019) and exposure to fewer viruses or a different viral community may result in population-wide differences in immune gene expression. Interactions amongst viruses within individual hosts and host communities appear to be complex (Viljakainen et al 2018) and it is therefore hard to disentangle the respective weight of viral loads and diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in line with the EICA framework and supported by our results of lower expression of certain immune pathways primarily targeted against viruses, relaxed viral pressure may allow reallocation of resources away from immunity to other functions that increase the invader's fitness. Furthermore, different types of viruses are known to trigger different physiological responses (Lester et al 2019). Therefore, plastic allocation of resources to specific immune responses with respect to variable viral exposure amongst regions may also increase the ant's competitive abilities and persistence of populations (Lester and Gruber 2016).…”
Section: Discussionmentioning
confidence: 99%